Determining the Aims of Economic Planning in Developing Countries and Problems of its Application - الاسدي, علي (Dirasat in Economics and Business, 1981)
The role of economic planning is increasing as one of the most effective means in the policy of economic development in developing countries. Although some developing countries successfully solve many of the technical problems involved in the compiling of their economic plans, there are many which are still facing these problems. One of the most important of these is how to establish a clearcut strategy and order of priorities. The planners, however, are faced with even more complex problems during the second stage: implementing the economic plan. Although there are many factors responsible for this state of affairs, we shall pinpoint only a few of them: economic mismanagement, the lack of commitment and low level of planning aareness, the poor state of statistical and scientific research, and finally the absence of bodies concerned with evaluating planning and its long term effects. These are all real obstacles to the realization of the economic plan.